2021
DOI: 10.1021/acsami.0c18670
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Thermal Stability and Solid Electrolyte Interphase on Na2Ti3O7/C as a Non-carbonaceous Anode Material for Sodium Storage Using Non-flammable Ether-based Electrolyte

Abstract: In order to become commercially viable, sodium-ion batteries need to deliver long cycle life with good capacity and energy density while still ensuring safety. Electrolyte plays a key role forming solid electrolyte interphase (SEI) layers at low potential, which affects the thermal stability and cycle life of the anode materials under consideration. In this study, an ether-based non-flammable electrolyte, 1 M NaBF4 in tetraglyme, is tested for sodium storage using a non-carbonaceous anode material Na2Ti3O7/C, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Full coin cells with Na 0.9 Cu 0.12 Ni 0.10 Fe 0.30 Mn 0.43 Ti 0.05 O 2 versus hard carbon demonstrated close to 200 Wh/kg (cathode+anode) using a nonflammable glyme-based electrolyte. 21 18650 Cells with the same configuration demonstrated an energy density of 62 Wh/kg cell and a stable storage performance for 100 cycles. Based on various electrochemical and material characterization experiments, considerable improvements in the structure and storage performance were observed by Ti 4+ and Ni 2+ substitution.…”
Section: O3-type Layered Oxidesmentioning
confidence: 97%
“…Full coin cells with Na 0.9 Cu 0.12 Ni 0.10 Fe 0.30 Mn 0.43 Ti 0.05 O 2 versus hard carbon demonstrated close to 200 Wh/kg (cathode+anode) using a nonflammable glyme-based electrolyte. 21 18650 Cells with the same configuration demonstrated an energy density of 62 Wh/kg cell and a stable storage performance for 100 cycles. Based on various electrochemical and material characterization experiments, considerable improvements in the structure and storage performance were observed by Ti 4+ and Ni 2+ substitution.…”
Section: O3-type Layered Oxidesmentioning
confidence: 97%
“…(2) In conducting the above studies, particular emphasis should be put on the effect of the electrolyte as it is known that there is an intimate relationship between the safety of a Li-ion cell and the electrolyte it contains [6,12]. Some recent results on large-scale Na-ion cells indicate that Na-ion electrolytes utilising high weight fractions of thermally stable solvents such as PC or Tetraglyme can indeed result in lower rates of heat generation or higher thresholds for onset of exothermic self-heating reactions [65][66][67][68] (3) Recently, some articles have analysed the economic potential of Na-ion batteries from a materials perspective [19][20][21]. Detailed life-cycle cost estimations for Na-ion batteries, focussing on not just material costs or resource availability, but other factors such as costs of shipping/storing Na-ion cells at 0 V, relative to Li-ion cells at 30% SOC, and also their recycling, would certainly be timely and illuminating for the alkali-ion battery community…”
Section: Summary and Future Studiesmentioning
confidence: 99%
“…Later, Du et al found that changing the electrolyte (1 M NaBF 4 in tetraglyme instead of 1 M NaClO 4 in ethylene carbonate (EC) and propylene carbonate (PC) (v/v = 1 : 1)) could increase ICE of Na 2 Ti 3 O 7 /C from 33% to 73%, however, the compromise behind this breakthrough is to increase the cut-off voltage, which greatly limits the release of capacity. 26…”
Section: Introductionmentioning
confidence: 99%
“…Later, Du et al found that changing the electrolyte (1 M NaBF 4 in tetraglyme instead of 1 M NaClO 4 in ethylene carbonate (EC) and propylene carbonate (PC) (v/v = 1 : 1)) could increase ICE of Na 2 Ti 3 O 7 /C from 33% to 73%, however, the compromise behind this breakthrough is to increase the cut-off voltage, which greatly limits the release of capacity. 26 To nd a more general approach, we turn our attention to the binders suitable for NTO. From the previously reported but rare literature, it has been demonstrated that PVdF undergoes dehydrouorination during the electrode preparation of NTO, 27 and the catalytic activity of titanate materials may affect the binder and electrolyte.…”
Section: Introductionmentioning
confidence: 99%